Development of Electronic-Based Students’ Worksheets (E-LKPD) with Wizer.Me Application In Informatics Subject - Yuliana, Dyan; Husna, Zahra Nafilatul; Astindari, Tri (The Future of Education Journal, 2025)
The educational process must be improved in accordance with advances in science and technology. This should be a strong motivation for educators to continue to develop their skills, especially technological skills, so that classroom learning remains relevant to the needs of today's workforce. One of them is by developing Electronic Student Worksheets (E-LKPD). The purpose of this study was to develop E-LKPD with the Wizer.me application and test its feasibility level in Informatics subjects for class X at MA Sarji Ar-Rasyid. This type of research uses the Borg and Gall R&D (Research and Development) model. The results of the study showed that the developed E-LKPD was declared feasible based on media expert validation with an average score of 94% in the "Very Feasible" category, material expert validation with an average score of 90% in the "Very Feasible" category, and user (student) assessment with an average score of 89.16% in the "Very Feasible" category. So it can be concluded that E-LKPD assisted by Wizer.me is feasible to be used in Informatics learning for class X MA Sarji Ar-Rasyid.